A Comprehensive Analysis of the significance of Blockchain and AI for IoT Security - Prof. Dr. Brahmananda S H, Rupali S. Vairagade (International Journal of Advanced Science and Technology, 2020)
Internet of Things (IoT) has been an epitome technology for connecting people seamlessly with devices. This technology is based on internet powered devices with privacy authentication things which update their status on a webserver either continuously or via event-triggering. IoT is used for all kinds of applications ranging from hobby projects to high-grade military systems. Some of these applications require less to no security while others require high level of security. IoT systems are not prone to physical hacking because most of these devices are placed in remote locations which are generally not human-accessible. Therefore, hackers and attackers use software vulnerability measures in order to trace the data from these IoT networks. Usually IoT powered systems are computationally light-weighted. Thus, cryptographic systems alone are not an efficient solution because they can be easily deciphered using high powered computing devices. Therefore, advanced but light weighted machine learning and artificial intelligence layers (AI) are needed to strengthen the security of the IoT network. Moreover, due to light weighted machine learning and AI layers, there might be some loopholes in the IoT security architecture. To this end, the blockchain peer-to-peer (P2P) architecture can be of enormous value. Thus, in this paper we review and analyses the effect of both blockchain and machine learning on IoT security systems. Also, different solutions for IoT security using blockchain and AI are compared in order to evaluate the most optimum security architecture for a given IoT application. Some recommendations are also made in order to further strengthen the security of the IoT systems.